Central serous chorioretinopathy in a patient of juxtapapillary excavation misdiagnosed as optic disc pit maculopathy. (1st November 2018) - Kumawat, Devesh; Anjum, Shahnaz; Sahay, Pranita; Chawla, Rohan
Abstract : A 29-year-old healthy man had blurring of vision in the left eye for the past 2 months and was referred for the surgical management of optic disc pit maculopathy. Colour fundus examination and optical coherence tomography (OCT) revealed a large deep retinochoroidal excavation close to the temporal edge of the optic disc with an isolated central neurosensory detachment at the macula with underlying multiple small pigment epithelium detachments in the absence of retinoschisis. Fundus fluorescein angiography (FFA) confirmed the presence of multi-focal leakage at the macula and pooling into subretinal space in the form of a 'smoke-stack'. A correct diagnosis of juxtapapillary excavation and central serous chorioretinopathy was made and lifestyle modifications were advised in view of the acute episode. The clinical signs, OCT and FFA feature helped in the differentiation and appropriate management of maculopathy in this case.